MORPHOLOGICAL AND FUNCTIONAL MUCOUS LAYER CONDITION OF STOMACH AND DUODENUM IN PATIENTS WITH DIABETES MELLITUS - Krivonosova, E.M. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
It was performed the investigation  of gastric and duodenal mucous layer functional condition in patients with insulindependent diabetes mellitus. It was  characterized pH-metric, endoscopic and pathomorphologicpercularities of gastroduodenal system on a background of diabetic gastropathy, chronic gastritis and duodenal ulcer. The conclusion about expediency of H. pylori eradication therapy, metabolic, prokinetic and immunotrophic medications assignment for the treatment of diabetic patients with gastrodudenal disorders.